THE ROLE OF RISK TOLERANCE IN MODERATING THE EFFECT OF FINANCIAL ATTITUDE ON FINANCIAL BEHAVIOR - Elizabeth Maeko Cyrilla Handijaya; I Gusti Bagus Yosia Wiryakusuma (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to explain the effect of risk tolerance in moderating financial attitudes and financial behavior among young people in Surabaya and its surroundings. The method used is a quantitative approach. Primary data collection was carried out using a survey method using a questionnaire. The type of questionnaire used in this study is an online questionnaire and then distributed through various social media. The method used in this study uses the Partial Least Square (PLS) analysis method using SmartPLS software. Respondents consisted of 190 young people who live in Surabaya and its surroundings. The study result concluded that financial attitude affect financial behavior. However, risk tolerance does not moderate financial attitude and financial behavior. Other findings found that risk tolerance affects financial behavior.